Themes in the Philosophy of Music - Davies, Stephen (Oxford Oxford University Press, 2003)
Representing Stephen Davies's best shorter writings, these essays outline developments within the philosophy of music over the last two decades, and summarize the state of play at the beginning of a new century. Including two new and previously unpublished pieces, they address both perennial questions and contemporary controversies, such as that over the 'authentic performance' movement, and the impact of modern technology on the presentation and reception of musical works. Rather than attempting to reduce musical works to a single type, Davies recognizes a great variety of kinds, and a complementary range of possibilities for their rendition.
Keywords: Music philosophy and esthetics